Rules on the Web: Research and Applications 6th International Symposium, RuleML 2012, Montpellier, France, August 27-29, 2012. Proceedings - Bikakis, Antonis; Giurca, Adrian; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2012)
This book constitutes the refereed proceedings of the International RuleML Symposium, RuleML 2012, held in Montpellier, France, in August 2012 - collocated with the 20th biennial European Conference on Artificial Intelligence, ECAI 2012. The 14 full papers, 8 short papers and 2 track papers presented together with 2 keynote talks were carefully reviewed and selected from numerous submissions. The accepted papers address topics such as business rules and processes; rule-based event processing and reaction rules; rule-based policies and agents on the pragmatic web; rules and the semantic web; rule markup languages and rule interchange; and rule transformation, extraction and learning.
Business rules and processes -- rule-based event processing and reaction rules -- rule-based policies and agents on the pragmatic web -- rules and the semantic web -- rule markup languages and rule interchange -- rule transformation, extraction and learning.
Keywords: Computer science; Computer Communication Networks; Software engineering; Database management; Artificial intelligence; Computer Science; Information Systems Applications (incl. Internet).; Artificial Intelligence (incl. Robotics).; Computer Communication Networks; Software Engineering; Programming Techniques; Database Management